2023
DOI: 10.1017/jns.2023.20
|View full text |Cite
|
Sign up to set email alerts
|

Identification of anthropometric surrogate measurements and their cut-off points for the detection of low birth weight and premature newborn babies using ROC Analysis

Abstract: Despite the fact that health facilities in Ethiopia are being built closer to communities in all regions, the proportion of home deliveries remains high, and there are no studies being conducted to identify low birth weight (LBW) and premature newborn babies using simple, best, alternative, and appropriate anthropometric measurement in the study area. The objective of the present study was to find the simple, best, and alternative anthropometric measurement and identified its cut-off points for detecting LBW a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 23 publications
(35 reference statements)
7
0
2
Order By: Relevance
“…The possible reason for this discrepancy may be due to difference in socio-demographic characteristics and population variation between these studies. The above finding is also different from the findings of a study conducted in Eastern Ethiopia, which reported a mean and standard deviation of 8.7 (±1.4) cm ( 19 ). The possible reason for this difference may be due to the difference in socio-demographic characteristics between the two studies.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The possible reason for this discrepancy may be due to difference in socio-demographic characteristics and population variation between these studies. The above finding is also different from the findings of a study conducted in Eastern Ethiopia, which reported a mean and standard deviation of 8.7 (±1.4) cm ( 19 ). The possible reason for this difference may be due to the difference in socio-demographic characteristics between the two studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study revealed a chest circumference mean and standard deviation of 31.54 (±1.71) cm. This finding is consistent with the findings of a study conducted in Dire Dawa (Ethiopia) and India, which reported 31.7 (±3.09) cm and 31.85 cm (±2.19) cm, respectively ( 19 , 21 ). This finding is close to the findings of a study conducted in Jimma University Medical Center, which showed a mean and standard deviation of 32.7 (±2.3) cm ( 17 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations